Development of Walking indicators to advance the quality of spinal cord injury rehabilitation: SCI-High Project. (30th September 2019) - Musselman, Kristin E.; Verrier, Molly C.; Flett, Heather; Nadeau, Sylvie; Yang, Jaynie F.; Farahani, Farnoosh; Alavinia, S. Mohammad; Omidvar, Maryam; Wiest, Matheus J.; Craven, B. Catharine
Abstract : Objective: To describe the development of structure, process and outcome indicators that will advance the quality of walking rehabilitation for Canadians with spinal cord injury or disease (SCI/D) by 2020. Method: A framework for the evaluation of the quality of walking rehabilitation was developed by experts in walking after SCI/D. A systematic literature review identified factors influencing walking outcomes and potential walking indicators. A Driver diagram analysis summarized the factors affecting walking outcomes and subsequently informed the selection of structure and process indicators. Psychometric properties and clinical utility of potential walking indicators were considered during the selection of outcome indicators. Results: The structure indicator is the number of physical therapists using evidence-based walking interventions per number of ambulatory individuals with SCI/D. The process indicator is the number of received hours of walking interventions during inpatient rehabilitation per number of ambulatory individuals with SCI/D. The intermediary outcome indicator, which is collected at discharge from inpatient rehabilitation, is either the modified Timed Up and Go or the 10-Meter Walk Test, the choice of measure is dictated by the stage of walking recovery, as defined by the Standing and Walking Assessment Tool. The final outcome indicator, collected at 18 months post-discharge, is the Spinal Cord Independence Measure III-Mobility subscale. Conclusion: The selected indicators align with current clinical practice in Canada. The indicators will direct the timing and enhance the volume of walking therapy delivered, to ultimately increase the proportion of patients who achieve their walking potential by 18 months post-rehabilitation.